2011
DOI: 10.1016/j.clinph.2011.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Trained modulation of sensorimotor rhythms can affect reaction time

Abstract: Objective Brain-computer interface (BCI) technology might be useful for rehabilitation of motor function. This speculation is based on the premise that modifying the EEG will modify behavior, a proposition for which there is limited empirical data. The present study examined the possibility that voluntary modulation of sensorimotor rhythm (SMR) can affect motor behavior in normal human subjects. Methods Six individuals performed a cued-reaction task with variable warning periods. A typical variable foreperio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…The functional meaning of SMR requires further investigation by comparing the best and worst performance within highly skilled performers. Although some studies have found that higher SMR power was related to superior attentional performance (Egner & Gruzelier, 2001Hoedlmoser et al, 2008), others have indicated that SMR was not essential in musical performance or for an audiovisual Go/NoGo cursor movement task (Boulay, Sarnacki, Wolpaw, & McFarland, 2011). Additionally, EEG provides real-time cortical processing information during motor performance (Divekar & John, 2013), but it is limited in its ability to generate information on how the sensorimotor cortex works with the other relevant regions during motor execution (Thompson, Steffert, Ros, Leach, & Gruzelier, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The functional meaning of SMR requires further investigation by comparing the best and worst performance within highly skilled performers. Although some studies have found that higher SMR power was related to superior attentional performance (Egner & Gruzelier, 2001Hoedlmoser et al, 2008), others have indicated that SMR was not essential in musical performance or for an audiovisual Go/NoGo cursor movement task (Boulay, Sarnacki, Wolpaw, & McFarland, 2011). Additionally, EEG provides real-time cortical processing information during motor performance (Divekar & John, 2013), but it is limited in its ability to generate information on how the sensorimotor cortex works with the other relevant regions during motor execution (Thompson, Steffert, Ros, Leach, & Gruzelier, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that repeated use of a BMI can promote the neural plasticity of motor maps and increase functional connectivity influencing motor behavior, eg, reaction time (Boulay et al, 2011). Based on this finding, BMIs are currently being tested as therapeutic tools for various brain disorders, such as attention-deficit disorder (Lim et al, 2012), epilepsy (Strehl et al, 2014), and depression (Zotev et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Neurofeedback also has documented results for cognitive and memory enhancement in normal individuals (Angelakis et al, 2007;Boulay, Sarnacki, Wolpaw, & McFarland, 2011;Egner, Strawson, & Gruzelier, 2002;Fritson, Wadkins, Gerdes, & Hof, 2007;Gruzelier, Egner, & Vernon, 2006;Hanslmayer, Sauseng, Doppelmayr, Schabus, & Klimesch, 2005;Hoedlmoser et al, 2008;Keizer, Verment, & Hommel, 2010;Rasey, Lubar, McIntyre, Zoffuto & Abbott, 1996;Vernon et al, 2003;Zoefel, Huster, & Herrmann, 2010). Neurofeedback to enhance cognitive functioning and to counter the effects of aging has been referred to as ''brain brightening'' (Budzynski, 1996).…”
Section: Cognitive and Memory Enhancementmentioning
confidence: 99%